Principal’s Transformational Leadership in Shaping Innovative School Culture in the Digital Era - Connie Connie; Muhammad Kristiawan; Septi Emilya (Journal of Social Work and Science Education, 2026)
This research aims to investigate in depth how school principals with transformational leadership styles shape innovative school cultures in the digital era. This research responds to the gap of previous research that focused more on structural and administrative aspects in educational leadership, but has not explored exploratively the dynamics of transformational leadership in building a technology-oriented innovation culture. The method used is a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observations, and documentation studies at SMP Negeri 1, 2, 4, 9, 13 Bengkulu City that have implemented technology integration in learning and management activities. The results of this study show that school principals play the role of agents of change who inspire, facilitate collaboration, and create an open climate for renewal. The novelty of this study lies in mapping transformational leadership practices that are contextual with the challenges of digitizing education. The practical implications of this research encourage the development of leadership programs that focus on digital literacy and school cultural innovation. A major contribution of this research is the provision of a conceptual framework for transformative leadership in the context of 21st century digital schools.